HUBUNGAN ANTARA SELF REGULATED LEARNING DENGAN PROKRASTINASI AKADEMIK PADA MAHASISWA PENDIDIKAN KIMIA DI MASA PANDEMI COVID-19 - Rizkyani, Arivia Monique; Feronika, Tonih; Saridewi, Nanda (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
RELATIONSHIP BETWEEN SELF REGULATED LEARNING AND ACADEMIC PROCRASTINATION IN CHEMISTRY EDUCATION STUDENTS IN THE COVID-19 PANDEMIC AbstractThe world, including Indonesia, is being hit by the covid-19 outbreak, making students adapt to a new learning process, namely online. Students need self-regulated learning to direct the learning process to achieve optimal learning goals and suppress the level of academic procrastination experienced by students during the covid-19 pandemic. This study aims to determine the relationship between self-regulated learning and academic procrastination in Chemistry Education students during the covid-19 pandemic. This study uses a correlational method with a quantitative research approach. This study's population was 210 students of Chemistry Education class 2017, 2018, and 2019 with a sample size of 68 students who were determined using the proportional stratified random sampling technique. The instruments used were self-regulated learning questionnaires, academic procrastination questionnaires, and interviews. The product-moment correlation technique is used to test the hypothesis. The results obtained a correlation coefficient value of -0.409 with a significance of 0.001, so it can be said that there is a negative and significant relationship between self-regulated learning and academic procrastination in Chemistry Education students during the covid-19 pandemic. Abstrak Saat ini dunia termasuk Indonesia sedang dilanda wabah covid-19 yang membuat mahasiswa harus beradaptasi dengan proses pembelajaran baru yakni melalui daring. Mahasiswa membutuhkan kemampuan self regulated learning untuk mengarahkan proses belajar dalam mencapai tujuan pembelajaran yang optimal serta untuk menekan tingkat prokrastinasi akademik yang dialami mahasiswa pada masa pandemi covid-19. Penelitian ini. bertujuan untuk. mengetahui. hubungan antara. self regulated.learning dengan. Prokrastinasi. akademik pada mahasiswa. Pendidikan Kimia di.masa pandemi covid-19. Penelitian ini menggunakan metode korelasional dengan pendekatan penelitian kuantitatif. Populasi penelitian ini adalah mahasiswa Pendidikan Kimia angkatan 2017, 2018, dan 2019 berjumlah 210 mahasiswa dengan jumlah sampel sebanyak 68 mahasiswa yang ditentukan menggunakan teknik proportional stratified random sampling. Instrumen yang digunakan berupa angket self regulated learning, angket prokrastinasi akademik, dan wawancara. Teknik korelasi product moment digunakan untuk menguji hipotesis. Hasil penelitian diperoleh nilai .koefisien korelasi sebesar. – 0,409 dengan. signifikansi 0,001 sehingga.dapat dikatakan bahwa terdapat hubungan.negatif dan signifikan.antara self. regulated. learning dengan prokrastinasi akademik pada. mahasiswa Pendidikan Kimia di.masa pandemi covid-19.